2019
DOI: 10.1039/c9dt03587g
|View full text |Cite
|
Sign up to set email alerts
|

Complete post-synthetic modification of a spin crossover complex

Abstract: Complete post-synthetic (PS) modification of an iron–triazole SCO complex is reported; and a full characterization is carried out for a series of PS-SCO complexes with 23%–100% modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…To the best of our knowledge, concerning this family of compounds, only formations of imine by PSM methodology were described in the literature. [46][47][48]50] When it was possible, we also prepared corresponding materials using the direct synthesis (DS) method in order to ease the characterization of the desired compound.…”
Section: Syntheses Of Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, concerning this family of compounds, only formations of imine by PSM methodology were described in the literature. [46][47][48]50] When it was possible, we also prepared corresponding materials using the direct synthesis (DS) method in order to ease the characterization of the desired compound.…”
Section: Syntheses Of Complexesmentioning
confidence: 99%
“…Very recently, Costa et al [50] published a complete PSM method resulting from a reaction between the [Fe(NH 2 trz) 3 ]X 2 (X=OTs) complex and vapors of aldehyde or ketones. Following our previous results [46] for which a complete PSM reaction was achieved on an iron-triazole SCO complex [Fe(NH 2 trz) 3 ](NO 3 ) 2 (with NH 2 trz = 4-amino-1,2,4-triazole), we are interested to study the PSM methodology on this family of compounds with a variety of substrates, in order to confirm the efficiency and show the versatility of such approach. We selected this "parent material" since it has a lot of advantages, i. e. [53] 1) well-known and interesting SCO properties (above room temperature with a hysteresis loop); 2) it can be easily synthesized in one step from commercial reactants; 3) it has a NH 2 group which is able to react with several reagents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While exploring polymeric SCO materials, Bousseksou et al [53] demonstrated that covalent PAM and direct ligand synthesis produced functionalized products with different magnetic properties. Parent complex 57 is a coordination polymer featuring pendant amines that can undergo condensation reactions with aldehydes to produce imines (Scheme 17).…”
Section: Covalent Derivatization Of Supramolecular Complexesmentioning
confidence: 99%
“…Preparation of imine-functionalized SCO compound 58 by PAM of complex 57 and direct synthesis from ligand 59 afforded products with differing magnetic properties. [53] (a) Molecular model (UFF optimized) of the parent SCO complex 57, which is a solid-state coordination polymer featuring pendant amine groups. Key: greycarbon, bluenitrogen, whitehydrogen, orangeiron(II).…”
Section: Covalent Derivatization Of Supramolecular Complexesmentioning
confidence: 99%